KEANEKARAGAMAN JENIS DAN KELIMPAHAN ORGANISME SERANGGA DI HUTAN RAWA GAMBUT YANG DIKONVERSI MENJADI SAWAH DI PEAT TECHNO PARK UNIVERSITAS PALANGKA RAYA - Valentine Windy; Sulmin Gumiri; Yetrie Ludang (BIOSAPPHIRE: Jurnal Biologi dan Diversitas, 2023)
This study aims to identify the species diversity and abundance of insects in the peat swamp forest converted into rice fields in the Peat Techno Park, University of Palangka Raya. The sampling method used three types of traps, namely yellow trap, swing nets,and light traps. The Shanon -Weiner equation was used to calculate the diversity index of the collected insects. The insects that were caught consisted of 10 orders and 49 families with a total 0f 2,089 individuals. The most caught insects were the order Ephemeroptera with a total 730 individuals. The abundance index of Ephemeroptera was 35.04%, Formicidae 11.20%, Coenagrionidae 10,39%, and Tetragnathidae 9,38%. The four of this insects are classified as dominant. The H’ index is 2.5037 where the level of insect diversity is moderate, the dominance index is 0.1626 so that dominance is classified as moderate. The evenness index is 0.6276, which means moderate evenness.